The Characteristic of Toddlers with ARI Disease in Kanigaran Public Health Center, Probolinggo City - Badrus Sholeh; Peni Perdani Juliningrum; Ira Rahmawati (Nursing and Health Sciences Journal (NHSJ), 2022)
Toddlers are included in the age group that is very susceptible to infections, especially those that attack the respiratory tract. Acute respiratory infection (ARI) in developing countries is one of the factors that cause the high mortality rate for children under five. This study aims to describe the characteristics of children under five with ARI disease in the working area of the Kanigaran Health Center, Probolinggo City. The research design used this quantitative descriptive with a total sample of 146 medical record data. The sampling technique used a non-probability sampling technique with the quota sampling method. Collecting data using observation sheets. The results showed that toddlers with ARI were more common at the age of 1-3 years (71.2%), female gender (53.4%), non-LBW weight (88.4%), normal weight nutritional status (75 .3%), and complete status (57.5%). The characteristics of children under five in the Kanigaran Health Center Work Area, Probolinggo City are good. As a nurse, it is necessary to provide education to parents about the prevention of ARI, because currently, ARI has attacked many toddlers with good characteristics.